Legal education in Malaysia: should law teacher practice as lawyer? - Ayub, Zainal Amin; Mohamed Yusoff, Zuryati; Md Desa, Md Rejab; Abdul Wahab, Harlida (Medwell Journal, 2016)
The debate on the quality of legal teaching had been discussed for quite sometime.Malaysia is not an exception on this matter.It has been argued that one of the ways to improve legal education is by allowing law teacher to practice as lawyer concurrently with their teaching job at university.In Malaysia, law teachers do not have this privilege.This study examines the issue on this matter and the possibility for the legal academia in Malaysia to practice as lawyer. In so doing, comparison is made with the practice of the Malaysian neighboring country, Singapore as a source of critique.This study also discusses the challenges in allowing law teachers in Malaysia to practice as legal practitioners. The methodology applied in this study is doctrinal or pure legal research.This study found that allowing law teachers to also practice as lawyer is a way forward for Malaysia. The study also provides suggestion on how to allow law teachers to practice in Malaysia.